Adapting to the Future: Maritime and City Logistics in the Context of Digitalization and Sustainability - Carlos Jahn; Wolfgang Kersten; Christian M. Ringle (epubli GmbH, 2021)
This volume contains research contributions by an international group of authors addressing innovative and technology-based approaches for logistics and sustainability. They present simulation studies, systems and models for optimizations and digitalized solutions with a focus on maritime as well port and city logistics. This volume, edited by Carlos Jahn, Wolfgang Kersten, and Christian Ringle, provides valuable insights into digital transformation in logistics with regard to: - City Logistics - HICL and Practice - Excellence in Logistics and Supply Chain Management - Maritime Logistics - Port Logistics - Sustainability
urn:nbn:de:gbv:830-882.0162990; https://econpapers.repec.org/RePEc:zbw:hiclch:249645; https://econpapers.repec.org/RePEc:zbw:hiclch:249646; https://econpapers.repec.org/RePEc:zbw:hiclch:249647; https://econpapers.repec.org/RePEc:zbw:hiclch:249648; https://econpapers.repec.org/RePEc:zbw:hiclch:249649; https://econpapers.repec.org/RePEc:zbw:hiclch:249650; https://econpapers.repec.org/RePEc:zbw:hiclch:249651; https://econpapers.repec.org/RePEc:zbw:hiclch:249652; https://econpapers.repec.org/RePEc:zbw:hiclch:249653; https://econpapers.repec.org/RePEc:zbw:hiclch:249654; https://econpapers.repec.org/RePEc:zbw:hiclch:249655; https://econpapers.repec.org/RePEc:zbw:hiclch:249656; https://econpapers.repec.org/RePEc:zbw:hiclch:249657; https://econpapers.repec.org/RePEc:zbw:hiclch:249658; https://econpapers.repec.org/RePEc:zbw:hiclch:249659; https://econpapers.repec.org/RePEc:zbw:hiclch:249660; https://econpapers.repec.org/RePEc:zbw:hiclch:249661; https://econpapers.repec.org/RePEc:zbw:hiclch:249662; https://econpapers.repec.org/RePEc:zbw:hiclch:249663; https://econpapers.repec.org/RePEc:zbw:hiclch:249664; https://econpapers.repec.org/RePEc:zbw:hiclch:249665
Keywords: 650; City Logistics; HICL and Practice; Maritime Logistics; Port Logistics; Sustainability